Safety requirements for electrical equipment for measurement, control and laboratory use. Particular requirements for dry heat sterilizers using either hot air or hot inert gas for the treatment of medical materials, and for laboratory processes Part 2-043, (15th January 1998) - British Standards Institution,
No abstract available